Copper compound induces autophagy and apoptosis of glioma cells by reactive oxygen species and jnk activation - Trejo-Solís, Cristina (BioMed Central, 2012)
BACKGROUND: Glioblastoma multiforme (GBM) is the most aggressive of the primary brain tumors, with a grim prognosis despite intensive treatment. In the past decades, progress in research has not significantly increased overall survival rate. METHODS: The in vitro antineoplastic effect and mechanism of action of Casiopeina III-ia (Cas III-ia), a copper compound, on rat malignant glioma C6 cells was investigated. RESULTS: Cas III-ia significantly inhibited cell proliferation, inducing autophagy and apoptosis, which correlated with the formation of autophagic vacuoles, overexpression of LC3, Beclin 1, Atg 7, Bax and Bid proteins. A decrease was detected in the mitochondrial membrane potential and in the activity of caspase 3 and 8, together with the generation of intracellular reactive oxygen species (ROS) and increased activity of c-jun NH(2)-terminal kinase (JNK). The presence of 3-methyladenine (as selective autophagy inhibitor) increased the antineoplastic effect of Cas III-ia, while Z-VAD-FMK only showed partial protection from the antineoplastic effect induced by Cas III-ia, and ROS antioxidants (N-acetylcysteine) decreased apoptosis, autophagy and JNK activity. Moreover, the JNK –specific inhibitor SP600125 prevented Cas III-ia-induced cell death. CONCLUSIONS: Our data suggest that Cas III-ia induces cell death by autophagy and apoptosis, in part due to the activation of ROS –dependent JNK signaling. These findings support further studies of Cas III-ia as candidate for treatment of human malignant glioma.